Caliphate; is it Theological Inevitability or Sociological Experimentation? - M Ilham Kamil; Abdul Syatar; Muhammad Majdy Amiruddin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The main objective of this study was to investigate the ontological status of the caliphate as a sociological experimentation. The study was a library research which adopted a descriptive analytical method through reading various literatures with a philosophical historical approach. The data were obtained from a variety of credible literature and other various supporting information then presented with a strong analytical instrument based on the normative foundation and thoughts of the figures to generate a deeper elaboration of ideas. The result showed that the relationship between religion and the state was a matter of pure contact with public reason. The absence of religious sharih texts in state matters, including models and singular forms of state practice, is an indisputable reason for the profanity of the Khilafah. The state practices exemplified by the Prophet and Companions were nothing more than sociological experiments. The experiment of the Prophet and purely sociological relative is not a theological necessity. The state is in principle an institution designed to realize benefit as the highest moral principle and locus of the view of the universal will. As an alternative to the caliphate model which is outdated and impossible to revive, a democratic state is a realistic choice because it is in accordance with the development of modern life and is an effort to approach universal human values